Getting rural migrant children into school in South China: migrant agency and parenting. Issue 2 (4th May 2019) - Peng, Yinni
ABSTRACT: Scholarship has examined how immigrant parents in North America and Europe acculturate their children to the education system in their receiving societies, with a focus on overcoming language barriers and coping with cultural differences in education between home and host societies. However, relatively less attention has been paid to the efforts of migrant parents in circumventing structural obstacles to the education access of their migrant children. To address that gap, this study draws on the qualitative data obtained from 23 rural-urban migrants in South China to investigate how these parents help their migrant children access urban education resources in a social context where structural obstacles outweigh cultural/racial differences. This study defines migrant parents as active agents who use strategies and actions to adapt to, manoeuvre within or circumvent the structural constraints to augment urban education resources for their migrant children. The migrant parents' agency includes persistent efforts in obtaining urban hukou for their children; applying strategies to increase their children's qualification for public schools that use a point system; exploring guanxi and using tiger parenting to get their children into public schools; exchanging economic resources for education opportunities in elite private schools; purchasing extracurricular education services; and actively maintaining parent-teacher partnerships to support their children's schooling. While valuing the migrants' agency, this study also indicates that the efficacy of their actions and strategies is affected by disparities in their socioeconomic resources.